2016
DOI: 10.5812/jjm.36638
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Activities of Six Antifungal Drugs Against Candida glabrata Isolates: An Emerging Pathogen

Abstract: BackgroundCandida glabrata is a pathogenic yeast with several unique biological features and associated with an increased incidence rate of candidiasis. It exhibits a great degree of variation in its pathogenicity and antifungal susceptibility.ObjectivesThe aim of the present study was to evaluate the in vitro antifungal susceptibilities of the following six antifungal drugs against clinical C. glabrata strains: amphotericin B (AmB), ketoconazole (KTZ), fluconazole (FCZ), itraconazole (ITZ), voriconazole (VCZ)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 39 publications
(60 reference statements)
1
6
1
Order By: Relevance
“…Our results revealed that the highest resistance rate (13%) was associated with itraconazole, which is consistent with the studies of Shokohi et al (2011) (12.5%) and Espinel-Ingroff et al (2005) (17%). On the other hand, our results are inconsistent with those of Richter et al (2005) and Amirrajab et al (2016) who observed a resistance of up to 70% to itraconazole. This difference may be due to the difference in the source of samples and less prescription of antifungal drugs for the treatment of vaginal infections.…”
Section: Discussioncontrasting
confidence: 99%
“…Our results revealed that the highest resistance rate (13%) was associated with itraconazole, which is consistent with the studies of Shokohi et al (2011) (12.5%) and Espinel-Ingroff et al (2005) (17%). On the other hand, our results are inconsistent with those of Richter et al (2005) and Amirrajab et al (2016) who observed a resistance of up to 70% to itraconazole. This difference may be due to the difference in the source of samples and less prescription of antifungal drugs for the treatment of vaginal infections.…”
Section: Discussioncontrasting
confidence: 99%
“…As mentioned earlier, the samples had been collected in previous studies (references were cited) and were only molecularly confirmed in this study ( Figure 2 ). In the present research, based on the EUCAST guideline, the highest resistance rate to amphotericin B (20%) was observed at the MIC range of 0.25-4 µg/mL, MIC 90 of 4µg/mL, MIC 50 of 0.5 µg/mL, and geometric mean MIC of 0.44 µg/mL, which is similar to the previous reports [ 35 , 36 ]. This study indicated that 6.7% of the isolates were resistant (non-wild type) to posaconazole with an MIC range of 0.032-4 µg/mL, which is consistent with the results obtained by Badie et al .…”
Section: Discussionsupporting
confidence: 91%
“…Based on the results of the current study, caspofungin was an effective drug tested against C. glabrata with the MIC range of 0.032-1 µg/mL, MIC 90 of 0.5 µg/mL, MIC 50 of 0.5 µg/mL, and geometric mean MIC of 0.44 µg/mL that is in agreement with the results reported by Labbe et al . and other researchers [ 35 , 37 , 45 , 46 ]. Our study showed that MIC 90 values for fluconazole, posaconazole, and voriconazole were significantly lower than those obtained by Espinel-Ingroff et al .…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…In our previous study performed in Iran, the resistance rates of C. albicans strains to fluconazole, itraconazole, and voriconazole were obtained as 9.1%, 11.3% and 9.1%, respectively [35]. In another study, we reported fluconazole, itraconazole, and voriconazole resistance rates of 10%, 72.5%, and 37.5% for C. glabrata isolates, respectively [36].…”
Section: Discussionmentioning
confidence: 97%